LEGAL TERMINOLOGY FOR TRANSLATORS: COMPANY LAW. A BILINGUAL CORPUS-DRIVEN PROJECT - Bastos, Maria do Céu (2020)
In a world where people, goods, services, companies, and capital move globally, legal translation plays a crucial role because legal documents and rules regulate all these exchanges. Legal translation is acknowledged as a daunting and time-consuming task, due to the culture-bound nature of legal terms and the complexity of legal language. The aim of this article is to present a corpus-driven bilingual (British English and European Portuguese) terminology project in the domain of company law (company incorporation) with a view to translating company types and incorporation documents, as well as to understanding and deciding on the most suitable strategies to find equivalents in legal translation. As far as methodology is concerned, we follow the typical workflow of bilingual or multilingual terminology projects, according to the literature on the subject as well as terminology standards. The result is a termbase with the terms for company types and incorporation documents, which contains term records with relevant information for legal translators. We conclude that total equivalence is rare, but the concept of functional equivalence from comparative law constitutes a pragmatic approach to deal with it and that legal terminology should be translated using the terminology of the target legal system.